Hubungan Tingkat Pendidikan Dan Pengetahuan Ibu Dengan Sikap Ibu Dalam Pemberian Makanan Pendamping ASI (MP-ASI) Pada Bayi Usia 6-12 Bulan Di Medono Pekalongan - Hilda Prajayanti (Indonesian Journal on Medical Science, 2022)
The period from birth to two years of age is an important period for growth and development. Mother's education, knowledge and attitudes play a very important role, lack of mother's knowledge about how to maintain and care for good growth and development, often triggers malnourished children. This study aims to determine the relationship between mother's level of education and knowledge with mother's attitude in giving complementary feeding to infants aged 6-12 months in Medono Pekalongan. Correlative descriptive research design with a sample of 165 people. The results showed (60%) that the education of the respondents in this study was moderately educated, sufficiently knowledgeable (72.1%), and had a positive attitude in giving complementary feeding to infants aged 6-12 months (53.6%). The results of statistical tests showed that there was a relationship between education and attitudes in giving complementary feeding to infants aged 6-12 months (p; 0.003), and there was a relationship between knowledge and mother's attitude in giving complementary feeding to infants aged 6-12 months ( p:0.001).